Dioxin-like PCB 126 Increases Systemic Inflammation and Accelerates Atherosclerosis in Lean LDL Receptor-Deficient Mice. (1st December 2017) - Petriello, Michael C; Brandon, J Anthony; Hoffman, Jessie; Wang, Chunyan; Tripathi, Himi; Abdel-Latif, Ahmed; Ye, Xiang; Li, Xiangan; Yang, Liping; Lee, Eun; Soman, Sony; Barney, Jazmyne; et al.
Abstract: Exposure to dioxins and related persistent organic pollutants likely contributes to cardiovascular disease (CVD) risk through multiple mechanisms including the induction of chronic inflammation. Epidemiological studies have shown that leaner individuals may be more susceptible to the detrimental effects of lipophilic toxicants because they lack large adipose tissue depots that can accumulate and sequester these pollutants. This phenomenon complicates efforts to study mechanisms of pollutant-accelerated atherosclerosis in experimental animal models where high-fat feeding and adipose expansion limit the bioavailability of lipophilic pollutants. Here, we investigated whether a model dioxin-like pollutant, PCB 126, could increase inflammation and accelerate atherosclerosis in Ldlr–/– mice fed a low-fat atherogenic diet. We fed Ldlr –/– mice the Clinton/Cybulsky diet (10% kcal fat, 0.15% cholesterol) and sacrificed mice at 8, 10, or 12 weeks postPCB (2 doses of 1 μmol/kg) or vehicle gavage. To characterize this novel model, we examined the effects of PCB 126 on markers of systemic inflammation, hematological indices, fatty livers, and atherosclerotic lesion size. Mice exposed to PCB 126 exhibited significantly increased plasma inflammatory cytokine levels, increased circulating biomarkers of CVD, altered platelet, and red blood cell counts, increased accumulation of hepatic fatty acids, and accelerated atherosclerotic lesion formation in the aortic root. PCB 126 also increased circulating neutrophils, monocytes, and macrophages as determined by flow cytometry analysis. Exposure to dioxin-like PCB 126 increases inflammation and accelerates atherosclerosis in mice. This low-fat atherogenic diet may provide a useful tool to study the mechanisms linking exposure to lipophilic pollutants to increased risk of CVD.